Pemberdayaan Ibu Rumah Tangga Di Desa Trojalu Pada Masa Pandemi Covid-19 Melalui Pemanfaatan Media E-Commerce - Anita Handayani (Jurnal Pengabdian Manajemen, 2021)
At this time a wife or housewife is required to think more modern and creative to help improve family welfare. Because it is very important it is felt to provide education to housewives about the marketplace and e-commerce, so it is hoped that this activity can provide insight and knowledge to brands. The output target in this service activity is to provide skills to housewives in terms of training on the use of patchwork as masks, e-commerce literacy in the shopee marketplace with the hope that after having expertise and skills in e-commerce, they can improve the economy for family welfare.